(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The education of a reader through a piece of writing can take place in an environment of persecution or in one of freedom. Thus, the piece of writing may become exoteric, protreptic or elusive. Associative reading demands application and attention. Reading is an art exerted on language and thought. Several examples of reading comprehension becoming a fruitful philosophical action are analysed.